Application of calcium chloride on yield and quality of Capsicum annuum L. - Montri, N.; Sengseng, S.; Deewatthanawong, R.; Bunya-Atichart, K. (My University, 2024)
Application of calcium chloride on yield and quality of Capsicum annuum L. 'Super Hot' were investigated. The experiments were conducted in randomized complete block design (RCBD). 0, 20, 40, 60, 80, and 100 mg L-1calcium chloride was sprayed preharvest at the orange-red ripening stage. The ripe red fruits were harvested. Yield and quality in terms of fruit color and secondary compound content were measured. The results showed that spraying with various concentrations of calcium chloride did not affect the percentage of dry weight and color of fruit but significantly influenced fresh and dry weight, capsaicin, total phenolics, and total flavonoid contents. Preharvest spraying of calcium chloride at 40 mg L-1treatment gave the maximum fresh and dry weight and total phenolics at 1,257.83 g, 361.35 g, and 44.75 mg GAE g-1DW, respectively. A high content of total flavonoid at 63.50 and 6.75 mg QE g-1DW was observed in 20 to 40 mg L-1treatment, while high contents of capsaicin contents at 64.32 mg g-1 DW were achieved in 80 mg L-1,.
Keywords: calcium; capsaicin; chili; flavonoids; phenolics